PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING TERINTEGRASI LINGKUNGAN HIDUP PADA MATA KULIAH KONSEP DASAR IPS SEKOLAH DASAR - Nasution, Yusra; Sitohang, Risma; Khairunisa, Khairunisa (Universitas Negeri Medan, 2022)
The basic research objectives are: 1) To produce an E-Module based on Environmental Integrated Problem Based Learning in a valid Elementary School Social Sciences Basic Concept Course. 2) To test the viability of the Natural Coordinates Issue Based Learning-Based E-Module item within the Fundamental Social Sciences Rudimentary School Concept Course. The sort of investigate conducted is the sort of inquire about and improvement or Inquire about and Development (R&D). This investigate may be a investigate and advancement show utilizing the ADDIE (Examination, Plan, Improvement, Execution, and Evaluation) show. The area of the investigate was carried out within the PGSD FIP Unimed ponder program. The populace of this inquire about is all understudies of PGSD Unimed Stambuk 2021 totaling 225 understudies comprising of 11 (A-K) customary and expansion classes. The test of this investigate was carried out in a course program and one lesson was chosen, specifically Lesson J Normal 2021, totaling 28 understudies. Data collection techniques in this study using observation, interviews, questionnaires or questionnaires and documentation. The results showed that the feasibility assessment by media experts scored 87 (87%) with the